Leilões da transmissão de energia elétrica no Brasil de 1999 a 2006 : uma avaliação do aprendizado organizacional de segunda ordem - Goldman, Fernando Luiz (2008)
In business environments increasingly complex, characterized by globalization, importance of networks, hyper-competitive, hyper-information and by reduced life cycles of products, services and processes, innovation is seen as key to survival of organizations. Several theories have been put forward proposing solutions for organizations change and discover how to succeed with the innovations. This dissertation aims to contribute to the development of awareness of the importance for innovation to distinguish Organizational Learning of First and Second Order. It is assessed whether the analysis of the results of auctions of transmission between 1999 and 2006 contributed to the Organizational Learning in major regional companies of the group Eletrobrás. This search will clarify concepts and ideas about how, after a period of wrong emphasis in the tools of Information and Communications Technologies, Knowledge Management, by the creation of the organizational knowledge (innovation), has been perfoming as allowing of Organizational Learning.